Bionic enamel composite material, preparation method and application
Through multi-stage, multi-scale, multi-component ceramic hydroxyapatite nanowire/polymer organic polymer composite materials, the integrated repair problem of abutment and crown in the existing technology is solved, and high strength and toughness are achieved and viscoelastic bionic enamel composite materials improve the long-term effect and aesthetics of the implant and reduce the risk of complications.
Patent Information
- Application Number
- CN202410156793.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-02-04
AI Technical Summary
In the treatment of dental deficiencies, existing implant and restorative materials have insufficient comprehensive performance, making it difficult to achieve integrated repair of the abutment and crown, resulting in complications such as insufficient bonding interface, falling off, and breaking, and are not conducive to long-term use for patients with limited space. Effects may even lead to planting failure.
Using multi-stage, multi-scale, multi-component three-dimensional ceramic hydroxyapatite nanowire/polymer organic polymer block composite materials, bionic enamel composite with high strength, high toughness, high hardness and high viscosity elasticity Materials are used to make the upper crown and abutment of the implant, and the surface morphology structure of the material is used to optimize soft tissue healing and closure, realizing the integrated design of the abutment and the crown.
The bionic enamel composite material with mechanical properties close to that of natural teeth has improved the aesthetics of the upper part of the implant and the promotion of soft tissue healing, reduced the risk of complications, and improved the long-term effect of the implant.
Smart Images

Figure HDA0004697284920000011 
Figure HDA0004697284920000012 
Figure HDA0004697284920000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oral medical implant materials and relates to a bionic enamel composite material, a preparation method and an application thereof. Background Art
[0002] Implant restoration is an important means of treating tooth loss. According to statistics, the demand for dental implants in my country is as high as 40 million per year, and oral and maxillofacial health is restored through implant restoration. In the process of implant restoration of tooth loss, the upper part of the implant (abutment, crown) is the key to the success of implant restoration. At present, the commonly used abutment materials in clinical practice are titanium and titanium alloy materials, and the commonly used crown restoration materials are zirconium oxide, aluminum oxide or lithium disilicate all-ceramic materials. Metal materials are not conducive to the aesthetic restoration of teeth. All-ceramic materials have high elastic modulus, high hardness, high brittleness, low viscoelasticity, poor mechanical compatibility with natural teeth, and the risk of wear and fracture of the opposing natural teeth. Moreover, their structural composition is mostly concentrated in a single scale and a single component, resulting in insufficient comprehensive material performance, a functional gap with natural teeth, and it is impossible to achieve a material that meets the requirements of abutment + crown integrated restoration. The traditional crown manufacturing method is to design an integrated design, process the abutment and crown independently, and then bond them together, which may lead to common clinical complications such as insufficient bonding interface space, crown shedding, crown or abutment fracture, and adhesive overflow. In addition, for patients with limited implant restoration space, the separate restoration of the two often requires a larger occlusal space, which is difficult to complete. Therefore, it is difficult for the upper part of the implant to be truly bionic, which is not conducive to the long-term effect of the upper part of the implant restoration, and in severe cases, it may even lead to implant failure. In summary, the development of functional materials for upper part of the implant restoration that are consistent with the structure and mechanical properties of natural tooth components and realize the integrated design of the abutment and crown has important scientific significance and engineering value. Summary of the invention
[0003] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a bionic enamel composite material, a preparation method and an application thereof, as an upper restoration material for oral medical implants, for the integrated preparation of oral implant abutments and crowns. The present invention prepares and synthesizes a three-dimensional ceramic hydroxyapatite nanowire / polymer organic polymer block composite material with a multi-level, multi-scale, and multi-component overall oriented structure, and uses it for the production of upper implant crowns and abutment materials based on its high strength, high toughness, high hardness and high viscoelastic mechanical properties; then, using its surface morphology and structural advantages, explores the influence of the material surface microenvironment on soft tissue healing and closure, and thus provides design ideas and scientific basis for the "integrated" upper implant restoration scheme of bionic enamel materials for crown repair and soft tissue closure.
[0004] In the present invention, the multi-level refers to a matrix structure based on the oriented arrangement of ceramic hydroxyapatite nanowires; a reinforcement structure based on ceramic hydroxyapatite nanowires; and a crystal / amorphous interface structure based on crystalline ceramic hydroxyapatite nanowires and amorphous high molecular organic polymers.
[0005] The multi-scale refers to nanoscale design: the diameter of ceramic hydroxyapatite nanowires is 20-30nm; the crystal / amorphous interface constructed by crystalline ceramic hydroxyapatite nanowires / amorphous high molecular organic polymers (nanomechanical enhancement unit); micrometer scale design: micrometer-length ceramic hydroxyapatite nanowires are oriented and assembled with high molecular organic polymers to prepare a composite film with a thickness of 20-100μm (micrometer mechanical enhancement unit); macroscale design: the composite film is modularly assembled through a hot pressing process to prepare a ceramic hydroxyapatite nanowire / high molecular organic polymer composite material with a macroscale thickness.
[0006] The multiple components refer to an inorganic hydroxyapatite component, a high molecular polymer component, and an inorganic crystal / polymer amorphous interface component.
[0007] The overall oriented structure refers to the single orientation of hydroxyapatite in the high molecular polymer matrix.
[0008] The present invention discloses a bionic enamel composite material for the integrated production of an oral implant base and a crown, wherein the bionic enamel composite material contains ceramic hydroxyapatite nanowires as a crystalline reinforcement phase and a high molecular organic polymer as an amorphous toughening phase: the ceramic hydroxyapatite nanowires are micro-nano ceramic nanowires with a length of 5 to 10 μm and a diameter of 20 to 30 nm; the amorphous high molecular organic polymer is polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA) or silk protein, etc.
[0009] The bionic enamel composite material used for integrated production of an oral implant base and a crown has a hardness of 2.5 to 5.5 GPa, a modulus of 40 to 60 GPa, a viscoelastic loss factor of tanδ=0.03-0.04, and a viscoelastic quality factor of 1.5-2.5.
[0010] The present invention also provides a method for preparing a bionic enamel composite material having a multi-level, multi-scale, multi-component overall orientation structure for integrated production of an oral implant abutment and a crown, comprising the following steps:
[0011] Step 1, preparation of ceramic hydroxyapatite nanowires: mixing calcium salt and phosphate in a strong alkaline solution, heating, cooling, centrifuging and freeze-drying;
[0012] Step 2, preparation of a high molecular organic polymer solution: dissolving polyvinyl alcohol or silk protein in water; and / or dissolving polymethyl methacrylate in N,N-dimethylformamide or acetone to obtain a high molecular organic polymer solution;
[0013] Step 3: adding the ceramic hydroxyapatite nanowires obtained in the step 1 to the high molecular organic polymer solution obtained in the step 2 and stirring to form a suspension, pouring the suspension onto a glass substrate, brushing it unidirectionally to form a composite film, cutting, stacking, and hot pressing the composite film to obtain the bionic enamel composite material.
[0014] Specifically, step one further includes the following steps:
[0015] Step 1.1, mixing oleic acid, water and ethanol and stirring to obtain a mixed solution;
[0016] Step 1.2, dissolving sodium hydroxide, calcium chloride and sodium dihydrogen phosphate respectively with water, and then dropping them into the mixed solution obtained in step 1.1 in sequence after dissolution;
[0017] Step 1.3, heating for reaction, cooling and centrifuging, adding the centrifuged sample into an alkaline solution, heating and stirring for reaction;
[0018] Step 1.4: centrifuge the product sample obtained in step 1.3, and freeze-dry it to obtain ceramic hydroxyapatite nanowires.
[0019] In the step 1.1, the volume ratio of the oleic acid, the water and the ethanol is (5-15): (5-15): (5-7); the stirring time is 15-45 minutes, and the stirring speed is 100-500 r / min; preferably, the volume ratio of the oleic acid, the water and the ethanol is 10:5:5, the stirring time is 15 minutes, and the stirring speed is 200 r / min; and / or,
[0020] In the step 1.2, the mass concentration of the sodium hydroxide solution is 50-150 mg / mL, the mass concentration of the calcium chloride solution is 20-50 mg / mL, and the mass concentration of the sodium dihydrogen phosphate solution is 30-80 mg / mL; the amount of the sodium hydroxide solution added is 10-15 mL, the amount of the calcium chloride solution added is 10-15 mL, and the amount of the sodium dihydrogen phosphate solution added is 10-20 mL; after the addition is completed, stir for 10-30 minutes respectively, and the stirring speed is 100-500 r / min; preferably, the mass concentration of the sodium hydroxide solution is 95 mg / mL, the mass concentration of the calcium chloride solution is 30 mg / mL, and the mass concentration of the sodium dihydrogen phosphate solution is 50 mg / mL; the amount of the calcium chloride solution added is 10 mL, and the amount of the sodium dihydrogen phosphate solution added is 10 mL, and after the addition is completed, stir for 10 minutes respectively, and the stirring speed is 200 r / min; and / or,
[0021] In the step 1.3, the temperature of the heating reaction is 90-200°C, and the time of the heating reaction is 12-24h; the alkaline solution includes sodium hydroxide solution or potassium hydroxide solution; the reaction temperature of the heating and stirring reaction is 50-90°C, the reaction time of the heating and stirring reaction is 5-12h, and the stirring speed is 100-500r / min; preferably, the temperature of the heating reaction is 90°C, and the time of the heating reaction is 12h; the alkaline solution includes sodium hydroxide solution; the reaction temperature of the heating and stirring reaction is 50°C, and the reaction time of the heating and stirring reaction is 5h; the stirring speed is 200r / min; and / or,
[0022] In the step 1.4, the sample of step 1.3 is centrifuged and washed at a speed of 5000-10000 r / min, 3-8 times each time, 3-5 minutes each time. The centrifuged sample is freeze-dried for 24-48 hours before being collected. Preferably, the sample is centrifuged and washed at a speed of 8000 r / min, 3 times each time, 3 minutes each time; the centrifuged sample is freeze-dried for 48 hours before being collected.
[0023] In the step 2, the dissolution temperature of the polyvinyl alcohol or the silk protein is 25-50°C; and / or the dissolution temperature of the polymethyl methacrylate is 70-90°C; preferably, the dissolution temperature of the polyvinyl alcohol is 30°C; the dissolution temperature of the silk protein is 30°C; the dissolution temperature of the polymethyl methacrylate is 90°C; and / or,
[0024] The concentration of the high molecular organic polymer solution is 20 mg / mL-100 mg / mL; preferably, the concentration of the polyvinyl alcohol solution or the silk protein solution is 40 mg / mL; the concentration of the polymethyl methacrylate solution is 20 mg / mL; and / or,
[0025] In the step three, the suspension is stirred at a temperature of 20-50°C, the stirring speed is 200-600r / min, the stirring time is 12-48h, and the concentration of the ceramic hydroxyapatite nanowires in the high molecular organic polymer solution is 0.01g / mL-0.1g / mL; preferably, the suspension formed by adding the ceramic hydroxyapatite nanowires to the polyvinyl alcohol solution or the silk protein solution is stirred at a temperature of 30°C, the stirring speed is 200r / min, the stirring time is 48h, and the concentration of the ceramic hydroxyapatite nanowires in the polyvinyl alcohol solution or the silk protein solution is 0.04g / mL; and / or, the suspension formed by adding the ceramic hydroxyapatite nanowires to the polymethyl methacrylate is stirred at a temperature of 25°C, the stirring speed is 250r / min, the stirring time is 24h, and the final concentration of the ceramic hydroxyapatite nanowires in the polymethyl methacrylate solution is 0.05g / mL; and / or,
[0026] The temperature of the glass substrate is 70-120°C, and the speed of the one-way brushing is 1-3 cm / s; preferably, when the suspension components are the polyvinyl alcohol or the silk protein and the ceramic hydroxyapatite nanowires, the temperature of the glass substrate is 90°C, and the speed of the one-way brushing is 2 cm / s; and / or, when the suspension components are the polymethyl methacrylate and the ceramic hydroxyapatite nanowires, the temperature of the glass substrate is 100°C, and the speed of the one-way brushing is 1 cm / s; and / or,
[0027] The cutting size of the composite film is (2-10) cm×(2-10) cm; the temperature of the hot pressing is 40-60°C, the pressure of the hot pressing is 5-20 MPa, and the time of the hot pressing is 12-24 hours. Preferably, the cutting size of the composite film is 3 cm×3 cm square; when the composite film is prepared from the polyvinyl alcohol or the silk protein and the ceramic hydroxyapatite nanowires, the initial hot pressing temperature is 40°C, the hot pressing pressure is 5 MPa, and the hot pressing time is 12 hours, and then the hot pressing temperature is adjusted to 60°C, the hot pressing pressure is 20 MPa, and the hot pressing time is 24 hours; and / or, when the composite film is prepared from the polymethyl methacrylate and the ceramic hydroxyapatite nanowires, the hot pressing temperature is 40°C, the hot pressing pressure is 20 MPa, and the hot pressing time is 24 hours.
[0028] In a specific embodiment of the present invention,
[0029] 1) Ceramic hydroxyapatite nanowires (crystalline component synthesis), the nanowire size range is 20-30nm diameter, 5-10μm length crystalline phase hydroxyapatite, the synthesis process is as follows:
[0030] 1. Use a pipette to measure 5-15 mL of oleic acid, use a measuring cylinder to measure 5-15 mL of water and 5-7 mL of ethanol, add them to a beaker, and stir at room temperature for 15-45 minutes at a speed of 200 r / min;
[0031] 2. Weigh 10-22.5g of sodium hydroxide and dissolve it in 150-200mL of water. Stir it with ultrasonic until it is completely dissolved. Then use a measuring cylinder to measure 15mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 10-30min at a speed of 200r / min.
[0032] 3. Weigh 4-5g calcium chloride and dissolve it in 100-200mL water. Stir ultrasonically until completely dissolved. Then use a measuring cylinder to measure 10-15mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 10-30min at a speed of 200r / min.
[0033] 4. Weigh 7.5-16g of sodium dihydrogen phosphate and dissolve it in 200-250mL of water. Stir ultrasonically until it is completely dissolved. Then use a measuring cylinder to measure 10-20mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 10-30min at a speed of 200r / min.
[0034] 5. After stirring, transfer the sample to a 100 mL hydrothermal reactor and react at 90-200°C for 12-24 hours, then cool naturally after completion;
[0035] 6. Centrifuge the cooled sample, pour off the floating material on the lining of the hydrothermal kettle, rinse with water and pour into a 50mL centrifuge tube for centrifugation. After the sample is centrifuged, transfer it to a sodium hydroxide or potassium hydroxide solution with a small amount of water, stir at 50-90°C for 5-12h, and rotate at 200r / min;
[0036] 7. After stirring, centrifuge the sample, transfer it to a beaker with a small amount of water, stir it at room temperature, make up the volume, and freeze-dry it.
[0037] 2) A method for preparing a bionic enamel composite material for integrated production of an oral implant abutment and a crown, comprising the following steps:
[0038] 1. Dissolve high molecular weight PVA or silk protein in aqueous solution at 25-50°C; and / or dissolve PMMA in N,N-dimethylformamide at 70-90°C, and stir until completely dissolved to obtain a colorless transparent solution; the concentration of the obtained high molecular weight organic polymer is 20mg / mL-100mg / mL;
[0039] 2. Take the colorless transparent solution obtained in step 1, add the pre-prepared crystalline ceramic hydroxyapatite nanowires, and stir at 20-50°C until a uniform white suspension. The concentration of the ceramic hydroxyapatite nanowires in the colorless transparent high molecular organic polymer solution ranges from 0.01 g / mL to 0.1 g / mL;
[0040] 3. Pour the white suspension obtained in step 2 onto a pre-heated glass substrate, and use a commercial brush to apply a single-direction brush on the glass substrate at a temperature range of 70-120°C at a speed of about 1-3 cm / s. During the sliding process, as the high-temperature solution evaporates, a composite film is finally formed on the glass substrate;
[0041] 4. Cut the composite film obtained in step 3 into a certain size of (2-10) cm×(2-10) cm, spray a small amount of water or N,N-dimethyldiamide onto the surface of the film, laminate the film, and hot press it for 12-24 hours at a hot pressing temperature of 40-60°C and a hot pressing pressure of 5-20 MPa.
[0042] 5. Prepare a bionic enamel material with nanowires oriented parallel to each other, forming a micro-nano-sized topological structure and clear spatial anisotropy, which is similar to the crystal-amorphous structure of natural teeth and is used for the production of implant upper bases and crowns.
[0043] The present invention also provides the application of the bionic enamel composite material or the preparation method of the bionic enamel composite material in the preparation of clinical dental crowns in stomatology, upper healing abutments of oral implants, repair abutments and abutment-integrated crowns.
[0044] The beneficial effects of the present invention include: the present invention provides a bionic enamel composite material, which has the following advantages: 1) the prepared ceramic hydroxyapatite nanowires have uniform size and good crystallinity, 2) the crystalline ceramic hydroxyapatite nanowires and amorphous high molecular organic polymers are composited to construct a crystal / amorphous interface, 3) a large-scale composite film with a nanowire oriented structure can be prepared by a unidirectional brushing method, 4) the composite film is assembled into a macroscopic three-dimensional block material with a multi-level, multi-scale, and multi-component overall oriented structure through a simple, large-scale hot pressing process, and is used for the integrated design of the upper base of the implant and the crown. At the same time, a large block material (three-dimensional size reaches the centimeter level) can be macroscopically prepared, and the mechanical strength of the bionic enamel composite material is close to that of natural enamel, and can be used for the upper base of the implant (more beautiful than the metal base currently used on a large scale, and has a stronger effect of promoting soft tissue healing). BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0046] Figure 1 This is the morphology of the crystalline hydroxyapatite nanowires in Example 1.
[0047] Figure 2 It is a schematic diagram of the one-way brushing process of the present invention.
[0048] Figure 3 The XRD results show that the crystalline hydroxyapatite nanowire material retains the characteristic crystal peaks of the original crystalline hydroxyapatite nanowire after adding high molecular organic polymer.
[0049] Figure 4 This is an optical photograph of the bionic enamel composite material sample obtained in the present invention.
[0050] Figure 5 This is an immunofluorescence test after culturing fibroblasts on the surface of materials (pure titanium, non-oriented hybrid materials, and oriented bionic enamel materials), corresponding to the fluorescence staining results.
[0051] Figure 6 These are the two-dimensional mechanical data elastic modulus and hardness of the bionic enamel composite material for integrated production of an oral implant abutment and a dental crown obtained in Example 2 of the present invention.
[0052] Figure 7The tanδ value is the two-dimensional mechanical data of the bionic enamel composite material used for the integrated production of an oral implant abutment and a dental crown obtained in Example 2 of the present invention.
[0053] Figure 8 This is a scanning electron microscope photograph of the cross-section of the bionic enamel composite material for integrated manufacturing of an oral implant abutment and a dental crown obtained in Example 3 of the present invention after compression.
[0054] Fig. 9 The two-dimensional mechanical data of the bionic enamel composite material used for the integrated production of an oral implant abutment and a dental crown obtained in Example 3 of the present invention.
[0055] Fig.10 The two-dimensional mechanical data of the bionic enamel composite material used for the integrated production of an oral implant abutment and a dental crown obtained in Example 3 of the present invention.
[0056] Fig.11 This is a microscopic scanning electron microscope of the bionic enamel composite material for integrated production of an oral implant abutment and a dental crown obtained in Example 3 of the present invention.
[0057] Fig.12 The synthetic material of the present invention (oriented bionic enamel material) is compared with the non-oriented material and pure titanium material after culturing fibroblasts, and then the replication amount of the cell transcriptome RNA is extracted.
[0058] Fig.13 The present invention is used for the comparison of wound healing after the material of the present invention is implanted subcutaneously in the wound of mice. DETAILED DESCRIPTION
[0059] The present invention is further described in detail with reference to the following specific examples and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art and are not particularly limited by the present invention.
[0060] The technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present disclosure and its application or use. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0061] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0062] Characterization and detection of the bionic enamel composite material prepared in the present invention
[0063] 1) Preparation and performance testing of bionic enamel composite materials
[0064] 1. Nano-hydroxyapatite nanowires were prepared by the above method, and the crystal structure was confirmed by phase analysis using X-ray diffraction technology and transmission electron microscopy technology; scanning electron microscopy was used to characterize the surface structure morphology of the composite material, and the arrangement of nanowires on the surface of the composite material was preliminarily determined; Nano-CT testing was used to determine that the nanowire orientation structure inside the structure of the enamel-like composite material was orderly; Fourier transform infrared spectroscopy and Raman spectroscopy were used to characterize the changes in chemical bonds after the crystal-amorphous phase interface of the composite material was controlled.
[0065] 2. The synthetic crown / abutment integrated bionic enamel composite material must meet the following mechanical performance requirements: the hardness of the composite material is 2.5-5.5 GPa, the modulus can reach 40-60 GPa, the viscoelastic loss factor is tanδ=0.03-0.04, and the viscoelastic quality factor is 1.5-2.5.
[0066] 3. The layer thickness of the sample after hot pressing is 0.5-1.5 cm. The length and width are 2-3 cm respectively.
[0067] 2) Biological effects of materials
[0068] In vivo experiments using synthetic materials verify that the material has an in vivo soft tissue-promoting phenotype when used as an implant abutment; or in vitro experiments confirm that the material surface has a positive effect on the high expression of genes and proteins related to early cell adhesion and migration.
[0069] Example 1
[0070] Preparation of one-dimensional hydroxyapatite nanowires for the preparation of bionic enamel composite materials for the integrated production of oral implant abutments and crowns. The synthesis process is as follows:
[0071] 1. Use a pipette to measure 10 mL of oleic acid, use a measuring cylinder to measure 5 mL of water and 5 mL of ethanol, add them to a beaker, and stir at room temperature for 15 minutes at a speed of 200 r / min;
[0072] 2. Weigh 15g of sodium hydroxide and dissolve it in 175mL of water. Stir ultrasonically until it is completely dissolved. Then use a measuring cylinder to measure 15mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 15min at a speed of 200r / min.
[0073] 3. Weigh 2g of calcium chloride and dissolve it in 100mL of water. Stir it with ultrasonic until it is completely dissolved. Then use a measuring cylinder to measure 10mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 10min at a speed of 200r / min.
[0074] 4. Weigh 10g of sodium dihydrogen phosphate and dissolve it in 200mL of water. Stir it with ultrasonic until it is completely dissolved. Then use a measuring cylinder to measure 10mL of the solution and transfer it to the funnel and start adding it dropwise. After all the addition is completed, stir for 10min at a speed of 200r / min.
[0075] 5. After stirring, transfer the sample to a 100 mL hydrothermal reactor and react at 90 °C for 12 h. After completion, cool naturally.
[0076] 6. Centrifuge the cooled sample, pour off the floating material on the upper layer of the hydrothermal autoclave lining, rinse with water and pour into a 50mL centrifuge tube for centrifugation. After the sample is centrifuged, transfer it to a sodium hydroxide solution with a small amount of water, stir at 50°C for 5h, and rotate at 200r / min;
[0077] 7. After stirring, centrifuge the sample and wash it with water at a speed of 8000r / min, three times for three minutes each time; then transfer it to a beaker with a small amount of water, stir it at room temperature at a speed of 400r / min, fix the volume, and freeze-dry it for 48 hours.
[0078] In the present invention, the hydroxyapatite nanowires prepared in Example 1 are used. The test results show that the nanowires prepared in Example 1 have a width of 20 nm and a length of 8 μm (e.g. Figure 1 ). XRD characterization shows that it is a nanowire with good crystallinity (such as Figure 3 shown above).
[0079] Example 2
[0080] A method for preparing a bionic enamel composite material for integrated production of an oral implant abutment and a crown based on the directional assembly of one-dimensional hydroxyapatite nanowires and polymethyl methacrylate.
[0081] 1. Dissolve 1 g of polymethyl methacrylate in 50 mL of N,N-dimethylformamide in a water bath at 80°C and stir for 12 h at a stirring rate of 200 rpm to obtain a uniformly mixed colorless transparent solution with a concentration of 20 mg / mL;
[0082] 2. Take 20 mL of the solution obtained in step 1, add 0.5 g of hydroxyapatite nanowires (about 10 μm in length), and stir continuously for 24 h in a water bath at 25° C. at a stirring rate of 250 rpm to form a uniform white suspension;
[0083] 3. Use a commercial brush to dip the 50 mg / mL suspension prepared in step 2 and slide it in one direction on a glass substrate at a temperature of 100°C at a speed of about 1 cm / s (e.g. Figure 2 As shown in the figure, during the sliding process, as the high temperature solution evaporates, a composite film is finally formed on the glass substrate. The phase analysis of hydroxyapatite composite PMMA can be found in Figure 3 (below), it is particularly noteworthy that compared with pure HA, the composite material has a weak peak at 2θ=30°, which may be the peak of an amorphous polymer. Therefore, the composite material is a crystalline / amorphous composite product;
[0084] 4. The composite film obtained in step 3 is cut into a certain size, and the size after cutting is 3cm×3cm square. Then a small amount of N,N-dimethyldiamide is sprayed on the surface of the film. The film is stacked uniformly according to the scraping direction and hot pressed at 40℃ and about 20MPa for 24h (such as Figure 4 shown);
[0085] 5. The synthetic material was used to culture fibroblasts, and the fibroblast spreading and related cell membrane receptor expression were significantly better than those of the smooth pure titanium and non-oriented material groups. (e.g. Figure 5 )
[0086] In the present invention, quasi-static nanoindentation was used to test the bionic enamel composite material prepared in Example 2, and the indentation depth ranged from 100 to 600 nm. The test results showed that the two-dimensional hardness of the composite material prepared in Example 2 could reach 3 GPa, and the modulus could reach 60 GPa, which were comparable to the mechanical properties of real enamel (see Figure 6 As shown), its viscoelastic loss factor tanδ = 0.04 (as shown Figure 7 ). Observation of its surface and cross-sectional morphology proves that it has a highly oriented structure. Without the directional coating method, the surface morphology of the composite material shows a random arrangement state (see Figure 8 , the left is an ordered structure, and the right is an unordered structure).
[0087] Example 3
[0088] A method for preparing a bionic enamel composite material for the integrated production of an oral implant abutment and a crown based on the directional assembly of one-dimensional hydroxyapatite nanowires and polyvinyl alcohol.
[0089] 1. Dissolve 2 g of polyvinyl alcohol in 50 mL of deionized water in a 30°C water bath and stir for 8 h at a stirring rate of 250 rpm to obtain a uniformly mixed colorless transparent solution with a concentration of 40 mg / mL;
[0090] 2. Take 10 mL of the solution obtained in step 1, add 0.4 g of hydroxyapatite nanowires (about 8 μm in length), and stir continuously for 48 h in a water bath at 30° C. and a stirring rate of 200 rpm to form a uniform white suspension;
[0091] 3. Use a commercial brush to dip the 40 mg / mL suspension prepared in step 2, and apply a single-direction brush slide on a glass substrate at a temperature of 90°C at a speed of about 2 cm / s. During the sliding process, as the high-temperature solution evaporates, a composite film is finally formed on the glass substrate;
[0092] 4. The composite film obtained in step 3 is cut into a certain size, and the size after cutting is 3 cm × 3 cm square. Then a small amount of deionized water is sprayed on the surface of the film. The film is stacked uniformly according to the coating direction, and initially hot-pressed at 40°C and about 5 MPa for 12 hours, and then the heating temperature is adjusted to 60°C, and hot-pressed at 20 MPa for 24 hours;
[0093] 5. In the present invention, quasi-static nanoindentation was used to test the bionic enamel composite material prepared in Example 3, and the indentation depth ranged from 50 to 650 nm. The test results showed that the hardness of the composite material prepared in Example 3 could reach 2.5 GPa, and the modulus could reach 55 GPa, which were comparable to the mechanical properties of real enamel (e.g. Fig. 9 ), its viscoelastic quality coefficient E'tanδ=1.8 (such as Fig.10 ). Observation of its cross-sectional morphology proves that it has a highly oriented structure, such as Fig.11 shown.
[0094] 6. Use the material to culture fibroblasts, and the transcriptome RNA expression can be seen as follows Fig.12 As shown, genes ITGβ1 (integrin protein 1), COL 1 (type I collagen) and VCL (vinculin) related to cell spreading and tissue healing showed high expression on the surface of oriented bionic enamel materials (dark gray: titanium material; light gray: non-oriented material; black: oriented bionic enamel composite material).
[0095] 7. Different materials were implanted under the skin of mice, and it can be seen that the oriented bionic enamel composite material has a good ability to promote epidermal tissue healing (such as Fig.13 ).
[0096] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments.
[0097] As used in the present invention, the term "comprising" is an open expression, that is, including the contents specified in the present invention but not excluding other contents.
[0098] As used herein, the term "about" when applied to a value means that some slight imprecision in the value is allowed in the calculation or measurement (approximation of the accuracy of the value by some method; approximately or reasonably close to the value; nearly). If for some reason the imprecision specified by "about" is not understood in this conventional sense in the art, then "about" as used herein at least indicates the variation that may result from conventional methods of measuring or using such parameters.
[0099] As used in the present invention, the term "and / or" includes any and all combinations of one or more of the associated listed items. It is not intended to limit the present invention.
[0100] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A bionic enamel composite material, characterized in that: The bionic enamel composite material is a composite material of ceramic hydroxyapatite nanowires and high molecular organic polymers in a directional assembly, wherein the ceramic hydroxyapatite nanowires are oriented in a single manner in the high molecular organic polymer; the concentration of the ceramic hydroxyapatite nanowires in the high molecular organic polymer solution ranges from 0.01 g / mL to 0.1 g / mL; The bionic enamel composite material has a hardness of 2.5-5.5 GPa, a modulus of 40-60 GPa, a viscoelastic loss factor of tanδ=0.03-0.04, and a viscoelastic quality factor of 1.5-2.5; Wherein, the ceramic hydroxyapatite nanowire is in a crystalline phase, with a diameter of 20-30 nm and a length of 5-10 μm; Wherein, the high molecular organic polymer is an amorphous polymer, including polymethyl methacrylate, polyvinyl alcohol, and silk protein.
2. A method for preparing the bionic enamel composite material according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, preparation of ceramic hydroxyapatite nanowires: mixing calcium salt and phosphate in a strong alkaline solution, heating, cooling, centrifuging and freeze-drying; Step 2: Preparation of a high molecular organic polymer solution: dissolving polyvinyl alcohol or silk protein in water; or dissolving polymethyl methacrylate in N,N-dimethylformamide or acetone to obtain a high molecular organic polymer solution; Step 3: adding the ceramic hydroxyapatite nanowires obtained in the step 1 to the high molecular organic polymer solution obtained in the step 2 and stirring to form a suspension, pouring the suspension onto a glass substrate, brushing it unidirectionally to form a composite film, cutting, stacking, and hot pressing the composite film to obtain the bionic enamel composite material.
3. The preparation method according to claim 2, characterized in that: Step one further comprises the following steps: Step 1.1, mixing oleic acid, water and ethanol and stirring to obtain a mixed solution; Step 1.2, dissolving sodium hydroxide, calcium chloride and sodium dihydrogen phosphate respectively with water, and then dropping them into the mixed solution obtained in step 1.1 in sequence after dissolution; Step 1.3, heating for reaction, cooling and centrifuging, adding the centrifuged sample into an alkaline solution, heating and stirring for reaction; Step 1.4: centrifuge the product sample obtained in step 1.3, and freeze-dry it to obtain the ceramic hydroxyapatite nanowires.
4. The preparation method according to claim 3, characterized in that: In the step 1.1, the volume ratio of the oleic acid, the water and the ethanol is (5-15): (5-15): (5-7); the stirring time is 15-45 minutes; and / or, In the step 1.2, the mass concentration of the sodium hydroxide solution is 50-150 mg / mL, the mass concentration of the calcium chloride solution is 20-50 mg / mL, and the mass concentration of the sodium dihydrogen phosphate solution is 30-80 mg / mL; the amount of the sodium hydroxide solution added is 10-15 mL, the amount of the calcium chloride solution added is 10-15 mL, and the amount of the sodium dihydrogen phosphate solution added is 10-20 mL; after the addition is completed, stir for 10-30 minutes respectively; and / or, In the step 1.3, the temperature of the heating reaction is 90-200°C, and the time of the heating reaction is 12-24h; the alkaline solution includes sodium hydroxide solution or potassium hydroxide solution; the reaction temperature of the heating and stirring reaction is 50-90°C, and the reaction time of the heating and stirring reaction is 5-12h; the stirring speed is 100-500r / min; and / or, In the step 1.4, the sample of step 1.3 is centrifuged and washed at a rotation speed of 5000-10000 r / min, 3-8 times, each time for 3-5 minutes; the centrifuged sample is freeze-dried for 24-48 hours and then collected.
5. The preparation method according to claim 2, characterized in that: In the step 2, the dissolution temperature of the polyvinyl alcohol or the silk protein is 25-50° C., and the dissolution temperature of the polymethyl methacrylate is 70-90° C.; and / or, The concentration of the high molecular organic polymer solution is 20 mg / mL-100 mg / mL.
6. The preparation method according to claim 2, characterized in that: In the step 3, the suspension is stirred at a temperature of 20 to 50° C.; the stirring speed is 200 to 600 r / min; the stirring time is 12 to 48 h; the concentration of the ceramic hydroxyapatite nanowires in the high molecular organic polymer solution is 0.01 g / mL to 0.1 g / mL; and / or, The temperature of the glass substrate is 70-120° C., and the speed of the unidirectional brush coating is 1-3 cm / s; and / or, The cutting size of the composite film is (2-10) cm×(2-10) cm; the temperature of the hot pressing is 40-60° C., the pressure of the hot pressing is 5-20 MPa, and the time of the hot pressing is 12-24 h.
7. The bionic enamel composite material prepared by the preparation method according to any one of claims 2 to 6.
8. Application of the bionic enamel composite material according to claim 1 or 7, or the preparation method according to any one of claims 2 to 6, in the preparation of clinical dental crowns in stomatology, upper healing abutments of oral implants, repair abutments and abutment-in-one crowns.
Citation Information
Patent Citations
Inorganic wire material-organic polymer composite material and preparation method thereof
CN108892811A
Dental-enamel-like composite material based on one-dimensional nano-wire oriented assembly, and preparation method thereof
CN110255967A
Three-dimensional multistage highly-ordered hydroxyapatite super-long nanowire fiberboard-mud structure composite material, preparation method and application thereof
CN111635606A
Self-repairing lightweight high-strength composite material and preparation method thereof
CN117024895A
Enamel-like bionic composite material with multi-level substructure and preparation method of enamel-like bionic composite material
CN117752536A
